Competition among public good providers for donor rewards - Struwe, Natalie,Blanco, Esther,Walker, James (Research platform Empirical and Experimental Economics, University of Innsbruck, 2021)
We present experimental evidence for decision settings where public good providers compete for endogenous donations offered by outside donors. Donors receive benefits from public good provision but cannot provide the good themselves. The performance of three competition mechanisms is examined in relation to the level of public good provision and transfers offered by donors. In addition to a contest with rewards proportional to effort to all public good providers, we study two contests with exclusion from transfers, namely a winner-takes-all and a losergets-nothing. We compare behavior in these three decision settings to the default setting of no-transfers. Results for this novel decision environment with endogenous prizes show that contributions to the public good are not significantly different in the winner-takes-all and loser-gets-nothing settings, but donor's transfers are significantly lower in winner-takes-all. Initially, the winner-takes-all and loser-gets-nothing settings lead to a significant increase in public good contributions compared to the setting where transfers are proportional to contributions for everyone; but this difference diminishes over decision rounds. All three contest with endogenous prizes generate consistent and significantly higher public good provision compared to the setting with no-transfers.
10419/250151
Keywords: Graue Literatur; Public Good; Institution; Externality; Contests; Laboratory Experiment